Benefits of alignment quality-control processing steps and an Angiosperms353 phylogenomics pipeline applied to the Celastrales - Simmons, Mark P.; Maurin, Olivier; Bailey, Paul; Brewer, Grace E.; Roy, Shyamali; Lombardi, Julio A. [UNESP]; Forest, Félix; Baker, William J. (Wiley, 2022)
We examined the impact of successive alignment quality-control steps on downstream phylogenomic analyses. We applied a recently published phylogenomics pipeline that was developed for the Angiosperms353 target-sequence-capture probe set to the flowering plant order Celastrales. Our final dataset consists of 158 species, including at least one exemplar from all 109 currently recognized Celastrales genera. We performed nine quality-control steps and compared the inferred resolution, branch support, and topological congruence of the inferred gene and species trees with those generated after each of the first six steps. We describe and justify each of our quality-control steps, including manual masking, in detail so that they may be readily applied to other lineages. We found that highly supported clades could generally be relied upon even if stringent orthology and alignment quality-control measures had not been applied. But separate instances were identified, for both concatenation and coalescence, wherein a clade was highly supported before manual masking but then subsequently contradicted. These results are generally reassuring for broad-scale analyses that use phylogenomics pipelines, but also indicate that we cannot rely exclusively on these analyses to conclude how challenging phylogenetic problems are best resolved.